In patients undergoing fast track total knee arthroplasty, addition of buprenorphine to a femoral nerve block has no clinical advantage: A prospective, double-blinded, randomized, placebo controlled trial. Issue 27 (July 2017) - van Beek, Rienk; Zonneveldt, Harry J.; van der Ploeg, Tjeerd; Steens, Jeroen; Lirk, Phillip; Hollmann, Marcus W.
Abstract: Background: Several adjuvants have been proposed to prolong the effect of peripheral nerve blocks, one of which is buprenorphine. In this randomized double blinded placebo controlled trial we studied whether the addition of buprenorphine to a femoral nerve block prolongs analgesia in patients undergoing total knee arthroplasty in a fast track surgery protocol. Methods: The treatment group (B) was given an ultrasound-guided femoral nerve block with ropivacaine 0.2% and 0.3mg buprenorphine. We choose to use 2 control groups. Group R was given a femoral nerve block with ropivacaine 0.2% only. Group S also received 0.3 mg buprenorphine subcutaneously. Only patients with a successful block were enrolled in the study. Results: We found no difference in our primary outcome parameter of time to first rescue analgesic. We found lower opioid use and better sleep quality the first postoperative night in patients receiving buprenorphine perineurally or subcutaneously. Buprenorphine did not lead to any significant change in pain or mobilization. We found a high overall incidence of nausea and vomiting. Conclusion: In patients undergoing total knee arthroplasty, in the setting of a fast track surgery protocol, the addition of buprenorphine to a femoral nerve block did not prolong analgesia.